Assessment of the bioactivity of bioinspired magnesium oxide nanoparticles from the Azadirachta indica extract - Al-Harbi, Laila M.; Ezzeldien, Mohammed; Elhenawy, Ahmed A.; Said, Alaa Hassan (Frontiers in Bioengineering and Biotechnology, 2024)
Azadirachta indica (neem) extract was used to biologically synthesize magnesium oxide nanoparticles (MgO NPs). The synthesized NPs were characterized using X-ray diffraction (XRD), thermogravimetric analysis (TGA), transmission electron microscopy (TEM), scanning electron microscopy (SEM), Fourier-transform infrared (FTIR), and UV-vis spectroscopy. Antioxidant, anticancer, antibacterial, antidiabetic, and anti-inflammatory activities were analyzed for the synthesized MgO NPs and neem extract. The obtained results confirmed the synthesis of spherical magnesium oxide nanoparticles with an average particle size of 23 nm using XRD. The samples exhibited good thermal stability and high stability in biological media. Compared to the neem extract and chemically synthesized magnesium oxide nanoparticles, the bioinspired magnesium oxide nanoparticles showed considerable free radical scavenging activity, with an IC50 value of 69.03 μg/mL. In addition, they reflected high selectivity to liver hepatic cancer cells with an IC50 value of 94.85 μg/mL without inducing any damage to human umbilical vein endothelial cells. The antibacterial activity of the bioinspired magnesium oxide nanoparticles demonstrated comparable effectiveness in treating both Gram-positive and Gram-negative bacterial strains. Furthermore, the produced bioinspired magnesium oxide nanoparticles showed a high percentage of inhibition for both α-amylase and α-glucosidase enzymes with an IC50 value of 61. 53 and 50.6 μg/mL, respectively. In addition, the bioinspired magnesium oxide nanoparticles also showed a higher denaturation inhibition percentage with an IC50 value of 6.66 μg/mL, indicating strong anti-inflammatory action. These enhanced abilities usher in a new bioinspired magnesium oxide nanoparticle bio-application era. Consequently, further in vivo studies are needed to assess the kinetic properties of these nanoparticles.